The use of accruals to manage reported earnings: theory and evidence - Timothy W. Koch; Larry D. Wall (Federal Reserve Bank of Atlanta, 2000)
This paper develops a model in which firm managers maximize their own compensation by using accruals to manage reported earnings. The results of the model suggest that the form of the managerial compensation function and managerial time preferences may have an important influence on the relationship between accruals and latent earnings. Among the possible relationships suggested by the model are strategies we call Smooth Income, Occasional Big Bath, Live for Today, and Maximize Variability, each of which suggests a different reporting strategy pursued by managers. Most empirical tests of accruals are inconsistent with this and other theoretical models because they include a single earnings variable in a linear regression analysis. Instead, we document the reporting of accruals by two firms, Sunbeam and Citicorp, that is consistent with the "Live for Today" and "Occasional Big Bath" strategies.
Keywords: 330; Investments